REPRODIS: An Innovative Cloud-Based Interactive Platform to Improve Reproductive Health Knowledge of Adolescents with Intellectual Disabilities - Lusiana, Arum; Arfiana, Arfiana; Mundarti, Mundarti; Septiani, Ranny; Martini, Martini; Anggraini, Yetti (Poltekkes Kemenkes Tanjung Karang, 2025)
Adolescents with intellectual disabilities are a vulnerable group who often face barriers in accessing comprehensive reproductive health education. Limited communication skills, difficulty understanding abstract concepts, and social stigma hinder their ability to gain adequate knowledge, increasing the risk of sexual exploitation, early pregnancy, and sexually transmitted infections. Digital innovations have shown promise, yet cloud-based platforms tailored to this population remain limited. This study evaluated the effectiveness of the Reproductive Health Interactive System (REPRODIS), a cloud-based, interactive web platform, in improving adolescents with intellectual disabilities' reproductive health knowledge. A quasi-experimental one-group pre-test–post-test design was conducted with 30 adolescents aged 13–18 years with mild to moderate intellectual disabilities in a special needs school in Central Java, Indonesia. Participants completed a validated reproductive health knowledge questionnaire before and after four REPRODIS sessions delivered twice weekly over two weeks. The platform included simplified text, audio-visual animation, voice guidance, interactive quizzes, and parental monitoring features. Data were analyzed using a paired t-test with a significance level of 0.05. The mean knowledge score increased significantly from 46.3±8.2 (pre-test) to 73.5±7.9 (post-test) (p=0.001). More than 83% of participants improved by ≥20 points. Observations indicated higher engagement during REPRODIS sessions compared to conventional lectures, while parents reported greater confidence in discussing reproductive health at home. REPRODIS significantly improved reproductive health knowledge among adolescents with intellectual disabilities. This innovation demonstrates the potential of cloud-based interactive platforms as inclusive educational tools.